Assessment of serum ferritin levels in transfusion dependent thalassemic children on oral deferiprone in a tertiary care centre - Chirla, Suman; Wadhwa, Lalita; Wadhwa, Puneet (International Journal of Contemporary Pediatrics, 2019)
Background: Thalassemic patients require regular blood transfusions to maintain haemoglobin level around between 10gm/dl-15gm/dl, which would result in transfusional iron overload. The treatment of iron overload is carried out by using parenteral desferrioxamine (DFX) therapy or recently introduced oral Deferiprone (DFP,L1,Ferriprox,KELFER,CP20) an oral iron chelator, Oral deferiprone, DFP (3-hydroxy-1,2-dimethylpyridin-4-one) is a synthetic analogue of mimosine, an iron chelator isolated from the legume Mimosa paduca. Our study was undertaken to asses ferritin concentration in transfusion dependent thalassemic children on Deferiprone, attending thalassemia clinic in Anil Neerukonda hospital, Sanghivalasa, Visakhapatnam. Methods: The present study was a hospital based prospective study, 50 transfusion dependent thalassemic children on Deferiprone, attending thalassemia clinic in Anil Neerukonda hospital, Sanghivalasa, Visakhapatnam attached to NRI Medical College, Visakhapatnam were enrolled during the study period October 2017 and September 2018. Results: In our study authors found an increase in Serum ferritin concentration from 3067.99±1520.13 to 4281.10 ±1760.42 ng/ml at the end of 12 months, which was quite significant. Conclusion: Authors concluded that oral Deferiprone is not an effective iron chelation agent and is associated with complications like GI symptoms, joint pains in significant number of children. So, search for an alternative iron chelator or combined chelation therapies which are safe and cost effective should be continued.